Análise da relação deformação - metamorfismo em rochas pelíticas da Nappe de Luminárias, sul de Minas Gerais - Ferraz, Edson Ricardo Maia [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The metamorphic P-T conditions and their deformational structures of a high-pressure metamorphism zone were examined focusing on the petrology, thermodynamics and microtectonics of high-Al metapelitic rocks and metasedimentary rocks associated to the Luminárias Nappe, Southern Minas Gerais. The mineral assemblages found in the metapelites were Cld+Ky+St+Ms, St+Cld+Ms+Grt and Grt+St+Ky+Bt+Ms. The P-T conditions were calculated by pseudosections for the systems KFMASH and KFMASHTO and peak metamorphic temperatures were calculated by thermometry of the Zr in rutile. The results show that rocks on the northern portion of the study area underwent a medium amphibolite facies metamorphism (T= 590°C±60°C e P= 8.3±1.8 kbar; T= 570°C±20°C e P= 10±4.8) and the southern rocks were metamorphosed at the boundary of amphibolite and eclogite facies (T= 608°C±47°C e P= 11.8±2.8 kbar). The temperature values obtained based on the Zr-content were 575 °C e 636 °C, northern and southern areas, respectively. There are four ductile deformational phases in the area (D1, D2, D3 e D4). The metamorphic peak event is related to the D2 phase, interpreted as responsible for the nappe emplacement. These data allow us to say that these rocks were overburden at a depth approximately of 34 km up to 43 km within the Brasília Orogen. Sillimanites possibly related to the late interaction of the Ribeira Belt over the area were not recognized

As condições de P e T e as estruturas deformacionais em uma zona de metamorfismo de alta pressão, na Faixa Brasília, foram examinadas com foco em petrologia, termodinâmica e microtectônica dos metapelitos de alto alumínio e rochas metassedimentares associadas a Nappe de Luminárias, sul de Minas Gerais. As assembleias minerais presentes nos metapelitos são Cld+Ky+St+Ms, St+Cld+Ms+Grt e Grt+St+Ky+Bt+Ms. As condições de P e T foram estimadas por pseudosseções dos sistemas químicos KFMASH e KFMASHTO e a temperatura de pico metamórfico foi calculada por termometria de Zr nos rutilos. Os resultados mostram que as rochas da porção norte da área de estudos sofreram um metamorfismo da fácies anfibolito médio (T= 590°C±60°C e P= 8,3±1,8 kbar; T= 570°C±20°C e P= 10±4,8 kbar) e que as rochas da região sul foram submetidas a um metamorfismo no limite entre as fácies anfibolito e eclogito (T= 608°C±47°C e P= 11,8±2,8 kbar). Os valores de temperatura obtidos baseados no conteúdo de Zr foram 575 °C e 636 °C, norte e sul da área, respectivamente. Existem quatro fases de deformação dúctil registradas na área (D1, D2, D3 e D4). O pico metamórfico está associado com a fase D2, interpretada como responsável pelo transporte da nappe. Estes dados permitem dizer que estas rochas estiveram soterradas em profundidades aproximadamente entre 34 km a 43 km no interior do Orógeno Brasília. Não foram reconhecidas sillimanitas possivelmente associadas a atuação da Faixa Ribeira sobre a área
Keywords: Petrologia; Metamorfismo (Geologia); Rochas; Termodinamica; Geologia estrutural; Minas Gerais, Sul